Socioeconomic status and quality of life in population‐based Australian men: data from the Geelong Osteoporosis Study - Sharon L. Brennan; Lana J. Williams; Michael Berk; Julie A. Pasco (Elsevier, 2013)
Abstract Objective : To investigate the relationship between socioeconomic status (SES) and reported perceptions of quality of life (QOL) in a cross‐sectional population‐based analysis of a representative sample of Australian men. Methods : In 917 randomly recruited men aged 24-92 years, we measured QoL in the domains of physical health, psychological health, environment and social relationships, using the Australian World Health Organization Quality of Life Instrument (WHOQOL‐BREF). Residential addresses were cross‐referenced with Australian Bureau of Statistics 2006 census data to ascertain SES. Participants were categorised into lower, mid, or upper SES based on the Index of Relative Socioeconomic Disadvantage and Advantage (IRSAD), the Index of Economic Resources (IER), and the Index of Education and Occupation (IEO). Lifestyle and health information was self‐reported. Results : Males of lower SES reported poorer satisfaction with physical health (OR=0.6, 95%CI 0.4-0.9, p=0.02), psychological health (OR=0.4, 95%CI 0.3-0.7, p<0.001) and environment (OR=0.5, 95%CI 0.3-0.7, p<0.001), although not social relationships (p=0.59). The poorest QOL for each domain was observed in the lower and upper SES groups, representing an inverse U‐shaped pattern of association; however, statistical significance was only observed for psychological health (OR=0.5, 95%CI 0.4-0.7, p<0.001). These relationships were similar for IEO and IER. Conclusions : Men from lower and upper SES groups have lower QOL compared to their counterparts in the mid SES group.